PENGGUNAAN BAHAN AJAR BERBASIS PENDEKATAN SAINTIFIK MELALUI ICT DALAM MODEL PROBLEM BASED LEARNING TERHADAP KOMPETENSI FISIKA SISWA KELAS X SMAN 10 PADANG - Putri Melati; Masril Masril; Hidayati Hidayati (Universitas Negeri Padang, 2016)
Low competence of Physics students due to some factors; the lack of teachers’ concerns about students’ basic knowledge, the teachers are not common to reveal the real problems happened in the students’ environment, the learning material used have not based on the scientific approach, and the using of ICT has not been maximal yet. The aim of this research was to find out one solution of the problems above by using learning material based on scientific approach through ICT by applying PBL model which the purpose is to improve the students’ Physics competence at grade X of SMA N 10 Padang. This was a Queasy Experiment research with Factorial Design 2 X 2. The population was the students of grade X MIA in SMA N 10 Padang which registered at the Academic Year of 2015/2016. Samples were taken by using Purposive Sampling. The instruments are observation formats for competence of attitudes, post-test for competence of knowledge, and assessment rubric for competence of skill. The data obtained were analyzed by using graphical analysis for the competence of attitudes, two directions of variant analysis for the competence of knowledge and skill. Based on the data analysis, it can be concluded that there are significant differences of using learning material based on scientific approach through ICT by applying PBL model towards the students’ competence of attitudes, knowledge and skill at the significant degree of 95%.